Rape Beyond Crime - Kaplan, Margo (2017)
Public health experts agree that sexual violence constitutes a significant public health issue. Yet criminal law dominates rape law almost completely, with public health law playing at best a small supporting role. Recent civil law developments, such as university disciplinary proceedings, similarly fixate on how best to find and penalize perpetrators. As a result, rape law continues to spin its wheels in the same arguments and obstacles. This Article argues that, without broader cultural changes, criminal law faces a double bind: rape laws will either be ineffective or neglect the importance of individual culpability. Public health law provides more promising terrain for rape prevention because it is a strong legal framework that can engage the complex causes of rape, including the social norms that promote sexual aggression. While criminal law can only punish bad behavior, public health interventions can use the more effective prevention strategy of promoting positive behaviors and relationships. They can also address the myriad sexual behaviors and social determinants that increase the risk of rape but are outside the scope of criminal law. Perhaps most importantly, public health law relies on evidence-based interventions and the expertise of public health authorities to ensure that laws and policies are effective. Transforming rape law in this way provides a framework for legal feminism to undertake the unmet challenge of “theorizing yes,” that is, moving beyond how to protect women’s right to refuse sex and toward promoting and exploring positive models of sex. Criminal law is simply incapable of meeting this challenge because it concerns only what sex should not be. A public health framework can give the law a richer role in addressing the full spectrum of sexual attitudes and behaviors